DOES “THINKING IN SYSTEMS” FOSTER A CROSSDISCIPLINARY UNDERSTANDING OF ENERGY? - Yelva C. Larsen; Jorge Groß; Franz X. Bogner (European Scientific Journal, ESJ, 2015)
In school education the concept of energy should be a unifying element between all natural science disciplines. Still, many characteristics of living systems appear to be in contradiction to the laws of physics. Physics often refer to energy conservation in a closed system, whereas biology is often dominated by open ecological or physiological systems with a "dynamic equilibrium“. This makes the underlying, crosscutting scientific concept of energy hard to understand. Our study investigated if the idea of an open energy system (with an in- and output of energy), located within an “idealized” closed system (in which the total amount of energy is conserved), offers the potential for a cross-disciplinary understanding. We developed a learning environment and applied interviews to identify students’ ability to think in open and closed systems. Four teaching experiments with focus groups of three students each (9th grade, secondary school, males = 10) were carried out. Within the learning environment a scaled model illustrated the idea of an open system that is in direct exchange with the environment (representing an “idealized” closed system). We identified specific learning obstacles that are connected with energy conservation within the closed system, where students faced severe difficulties to detect the conversion of energy within the environment. A molecular perspective could “rebuild” the visibility and tangibility of energetic processes. We propose the particle model to bridge the apparent macroscopic – molecular gap.